Advances in Digital Holographic Interferometry - Viktor Petrov; Anastsiya Pogoda; Vladimir Sementin; Alexander Sevryugin; Egor Shalymov; Dmitrii Venediktov; Vladimir Venediktov (Journal of Imaging, 2022)
Holographic interferometry is a well-established field of science and optical engineering. It has a half-century history of successful implementation as the solution to numerous technical tasks and problems. However, fast progress in digital and computer holography has promoted it to a new level of possibilities and has opened brand new fields of its application. In this review paper, we consider some such new techniques and applications.